Blended Learning for The Higher Students at Post Pandemic, Why Not? - Khomarudin Khomarudin (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2023)
Covid 19 pandemic that has hit almost all over the world requires that the learning process at a Higher Education Institution be carried out online. The purpose of this study is to find out student responses to the online learning process during the Covid 19 pandemic, the second is how students respond to blended learning models that combine offline and online. The method used is descriptive qualitative. The researcher distributes questionnaires to students via Google forms related to learning during the Covid 19 pandemic and the blended learning model. The data that has been collected is then classified according to its type, analyse to explore the contents of the questionnaire, then concluded. From the results of the questionnaire, the researcher describes it to conclude. The results of the questionnaire show that students are starting to feel comfortable with online learning. The habit of online learning during the 2 years of the covid 19 pandemic provided valuable experience, finally they began to find comfort in online learning. As the learning process progresses through online media, students begin to find rhythm and comfort in online learning. Then the research data shows that more than 90% of respondents respond positively to learning with the blended learning model. In the blended learning model learning provides opportunities for students to adapt and develop soft skills in the field of technology. Some students also hope that 50% of the blended learning models will be used online and 50% offline. Based on the results of this research, blended learning is the choice of learning model after the pandemic.Keywords: Blended Learning, Covid 19, Higher Education